O‘QUVCHILARNI BAYON VA INSHO YOZISHGA O‘RGATISHNING O‘ZIGA XOS JIHATLARI - Najimova, A.D. (SCIENCE and SOCIETY, 2024)
In the article, what are the differences between a statement and an essay when teaching students to write a statement and an essay, as well as teaching them to compose a text, and what kind of work is done on the specific educational content in the primary-grade mother tongue classes it is mentioned that it should be carried out.
Keywords: primary grades; writing; statement; essay; text; difference